Empathic Communication Training to Increase Family Resilience - Mutingatu Sholichah; Sri Kushartati (Universitas Ahmad Dahlan, 2023)
As the smallest unit of society, the family inevitably encounters various challenges in supporting each member as they navigate their personal developmental tasks. As such, families must develop the ability to persevere through obstacles and adverse events, maintaining their function and role in society while demonstrating family resilience. This study uses an experimental method to investigate the effects of empathic communication training on increasing family resilience. Six families comprising 15 individuals participated in the study conducted in Kulon Progo, Indonesia. The assessment was conducted using a resilience scale and focused group discussion. The result demonstrates a significant increase in family resilience (Z= -2.226, p <0.05) following the emphatic communication training. Therefore, empathic communication training is a feasible alternative for enhancing family resilience.